2015
DOI: 10.4314/ajid.v10i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of hemorrhagic fever (Ebola) in Sierra Leone with ozone therapy

Abstract: Background: Ebola Virus Disease (EVD) has ravaged three countries in West Africa. The mortality rate is extremely high, and it is perceived not only as threat to all of Africa but to the entire world. There is no known treatment to date other than administration of convalescent blood or experimental monoclonal antibodies, which both often fail. Ozone therapy (OT) has been in clinical use for decades and has been found to have physiological effects, which should directly inactivate the virus itself, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Rectal ozone therapy led to the complete remission of symptoms after 7 days in 5 symptomatic patients infected with Ebola, the hemorrhagic fever virus with high lethality (65%; Rowen et al, 2016 ). It has also been observed that O 2 -O 3 therapy is able to kill SARS-CoV-1 virus in monkey cells in vitro and to benefit patients with bronchopneumonia and neurological complications ( Li et al, 2020a ; Ricevuti et al, 2020 ).…”
Section: Antiviral Action Of Omentioning
confidence: 99%
“…Rectal ozone therapy led to the complete remission of symptoms after 7 days in 5 symptomatic patients infected with Ebola, the hemorrhagic fever virus with high lethality (65%; Rowen et al, 2016 ). It has also been observed that O 2 -O 3 therapy is able to kill SARS-CoV-1 virus in monkey cells in vitro and to benefit patients with bronchopneumonia and neurological complications ( Li et al, 2020a ; Ricevuti et al, 2020 ).…”
Section: Antiviral Action Of Omentioning
confidence: 99%
“…All survived without any deterioration of symptoms after ozone therapy began, nor did they have any post Ebola complications. The epidemic claimed 60% of its victims and scarred survivors with a 70+% rate of complications [31]. The key method was directly administering oxygen/ozone gas intravenously (DIV), 20 cc at 30-55 mcg of ozone/cc of gas over a few minutes.…”
Section: Viral Vulnerabilitymentioning
confidence: 99%
“…Com relação aos mecanismos antivirais do ozônio, acredita-se que o gás cause oxidação das glicoproteínas da superfície viral ocasionando a ruptura do invólucro viral, interrompe o contato vírus com os receptores das células alvo e perturba o ciclo de reprodução, uma vez que inativa a enzima transcriptase reversa, sendo que todos eventos relatados ocorrem sem ocasionar citotoxicidade aparente (Carpendale & Freeberg, 1991;Wells et al, 1991). Ainda, é relatado estímulo no sistema imunológico com a administração da ozonioterapia (Rowen et al, 2016).…”
Section: Gás Ozônio Com Potencial Antiviralunclassified
“…Em 1991, Welles et al, em um estudo in vitro evidenciaram a inativação do vírus do HIV-1 utilizando soro tratado com ozônio (Wells, Latino, Gavalchin e Poiesz, 1991). Estudos mais recentes comprovam que o ozônio inativou tanto os vírus envelopados (cepa McIntyre do vírus do herpes simplex tipo 1 [HSV-1], vacinação cepa Elstree [VAC], vírus da estomatite vesicular cepa Indiana [VSV], cepa da gripe A [H1N1] A/WS/33) e vírus não envelopados (adenovírus humano tipo 2 [Ad2])(Valdenassi et al, 2020) Rowen et al (2016). administraram combinações de água ozonizada, ozônio intravenoso e retal em cinco pacientes com a doença do vírus Ebola por um período de 10 dias ou até a remissão do sintoma.…”
unclassified